Penjadwalan Produksi Untuk Meminimalkan Waktu Produksi Dengan Menggunakan Metode Branch And Bound - Nunung Indra Lesmana (Department Industrial Engineering, University of Muhammadiyah Malang, 2016)
Scheduling is the process of organizing, selecting and timing of the use of existing resources to produce output as expected within the expected time too. Problems faced by the company is determining the minimal production scheduling, as in the case of the production of the company in March, May and August 2015, delays occurred up to three business days, or approximately 14% compared to normal production time per month. The results of this study indicate if using methods Branch and Bound, the more processing time than the method the company trimmed. for example, in February 2016 when using the method of the company, the turnaround time is obtained 10584.385 minutes, whereas if the company uses Branch and Bound method can be reduced completion time of 789.66 minutes so that it becomes 9794.719 minutes, or 1.8 days faster than using companies.